2010
DOI: 10.4196/kjpp.2010.14.6.371
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofGlycyrrhizae Radixon Repeated Restraint Stress-induced Neurochemical and Behavioral Responses

Abstract: Glycyrrhizae radix (GR) is an herbal medicine that is commonly used in the East Asia for treating a variety of diseases, including stomach disorders. The objective of the present study was to examine the anti-stress effects of GR on repeated stress-induced alterations of anxiety, learning and memory in rats. Restraint stress was administered for 14 days (2 h/day) to the rats in the Control and GR groups (400 mg/kg/day, PO). Starting on the eighth day, the rats were tested for spatial memory on the Morris water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
(30 reference statements)
2
25
0
Order By: Relevance
“…increases in CRF immunoreactivity in the PVN but significantly decreased TH-like immunoreactivity in the LC. The TH enzyme is an important player in the stressinduced activation of the CNS and in stress-related psychopathological conditions, including anxiety (Park et al 2010). Therefore, the administration of EPT may regulate increases in anxiolytic-like behaviors in the EPM and OFT via the increased expression of TH in the LC, which is consistent with previous studies (Park et al 2010).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…increases in CRF immunoreactivity in the PVN but significantly decreased TH-like immunoreactivity in the LC. The TH enzyme is an important player in the stressinduced activation of the CNS and in stress-related psychopathological conditions, including anxiety (Park et al 2010). Therefore, the administration of EPT may regulate increases in anxiolytic-like behaviors in the EPM and OFT via the increased expression of TH in the LC, which is consistent with previous studies (Park et al 2010).…”
Section: Discussionsupporting
confidence: 84%
“…The TH enzyme is an important player in the stressinduced activation of the CNS and in stress-related psychopathological conditions, including anxiety (Park et al 2010). Therefore, the administration of EPT may regulate increases in anxiolytic-like behaviors in the EPM and OFT via the increased expression of TH in the LC, which is consistent with previous studies (Park et al 2010). Together, the present findings suggest that EPT attenuated the behaviors and neurochemical responses associated with anxiety by modulating the HPA axis and the central noradrenergic system.…”
Section: Discussionmentioning
confidence: 99%
“…This may have led to decrease in the number of arm entries in Y-maze test. This assumption is supported by published data (Park et al, 2010), although some studies showed an inverse relationship between avoidance and long-term spatial memory (He et al, 2011). The paradoxical stimulating effect of the irradiation on object recognition in 36Gy/6 group can also be associated with increased anxiety in this group.…”
Section: Discussionsupporting
confidence: 77%
“…Activation of the LC produces intense anxiety, hypervigilance and inhibition of exploratory behavior [24,25]. It has been proposed that clinical anxiety or depression may be the result of alterations in the activity of the LC in central noradrenergic system [26]. Thus, our results suggest that the central adrenergic system is involved in the antidepressant effect of BER on despair-like behavior that persisted for 3 days in rats following withdrawal from repeated morphine administration.…”
Section: Discussionmentioning
confidence: 55%